Analisis Usability pada Aplikasi Just Meme berdasarkan Model Nielsen - Pricilia, Cindy; Sudirman; Marlina (KHARISMA Tech, 2024)
Just Meme is a mobile-based digital platform where users can create or edit memes and share them on various social media platforms such as Instagram, WhatsApp, and other media-sharing applications available within the app. This research aims to analyze the level of usability of the Just Meme application. To determine the usability level of Just Meme, an analysis is conducted using Nielsen's model, which consists of five parameters: Learnability, Memorability, Efficiency, Error, and Satisfaction. Data collection is carried out through a Google Form questionnaire with a total of 37 respondents, and the statistical analysis is performed using IBM SPSS 26. The questionnaire used in this study is based on Nielsen's model to measure usability with the five main variables. The results of the analysis indicate that the efficiency and satisfaction variables have a positive and significant impact on usability. On the other hand, the learnability, memorability, and error variables have a positive but not significant impact on usability. Furthermore, these five variables collectively contribute 8.2% to the usability of Just Meme.